EFFECTS OF SYNBIOTIC SUPPLEMENTATION ON GUT FUNCTIONING AND SYSTEMIC INFLAMMATION OF COMMUNITY-DWELLING ELDERS - SECONDARY ANALYSES FROM A RANDOMIZED CLINICAL TRIAL - VALENTINI NETO,João (2020)
ABSTRACT BACKGROUND: Aging is a complex process marked by alterations on gut functioning and physiology, accompanied by an increase on the inflammatory status, leading to a scenario called “inflammaging”. OBJECTIVE: To evaluate the effects of a synbiotic substance on systemic inflammation, gut functioning of community-dwelling elders. METHODS: This is a secondary analysis from a randomized clinical trial, lasting 24 weeks, including 49 elders, distributed into two groups: SYN (n=25), which received a synbiotic substance (Frutooligossacaride 6g, Lactobacillus paracasei LPC-31 109 to 108 UFC, Lactobacillus rhamnosus HN001 109 to 108 UFC, Lactobacillus acidophilus NCFM 109 to 108 UFC e Bifidobacterium lactis HN019 109 to 108 UFC), or PLA (n=24), receiving placebo. The evaluations consisted of serum IL-10 e TNF-α (after overnight fasting), evaluation of chronic constipation (by Rome III Criteria) and faeces types (by Bristol Stool Form Scale). Data were compared before and after the supplementation time, and between groups. RESULTS: No significant differences were found between baseline and final values of serum inflammatory markers. Some subtle beneficial changes were observed in SYN, concerning both gut functioning and faeces types. CONCLUSION: From our data, synbiotic supplementation showed a subtle benefit in gut functioning in apparently healthy community-dwelling elders. Our findings can suggest that the benefits in healthy individuals were less expressive than the ones presented in studies with individuals previously diagnosed as dysbiosis. Future studies, comparing elders with and without gut dysbiosis can confirm our findings.